Clinical picture of multifocal chorioretinitis caused by Mycobacterium tuberculosis – case report - Turno-Kręcicka, Anna; Zatoński, Tomasz; Jabłonka-Strom, Agnieszka; Kręcicki, Tomasz (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
We present clinical picture of unusual case, of multifocal chorioretinitis due to tuberculosis. Twenty years old female was admitted to ENT department with cervical lymphadenopathy, profound dolorous tonsils enlargment resembling antibiotic resistant purulent tonsillitis and nasopharyngeal masses. The patient also reported transient vision disturbances. Lymph node and Waldeyer’s ring biopsy revealed tubercular granulomatosis with caseation, Gramm(+) bacteria, and Mycobacterium tuberculosis DNA presence by polymerase chain reaction testing.